2009
DOI: 10.1186/bf03352942
|View full text |Cite
|
Sign up to set email alerts
|

Seismic structure of the northern end of the Ryukyu Trench subduction zone, southeast of Kyushu, Japan

Abstract: P-wave velocity models related to the Philippine Sea plate subduction have been obtained from seismic explorations at the northern end of the Nansei-Shoto (Ryukyu) Trench. Both multi-channel seismic reflection and ocean bottom seismographic records provide clear images of the rough seafloor topography and irregular P-wave velocity structure of the northwestern extension of the Kyushu-Palau Ridge and Amami Plateau below the landward trench slope. Low velocity (V p ≤ 4-5 km/s) and thick (>7 km) materials above t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 9 publications
(12 reference statements)
1
25
0
1
Order By: Relevance
“…However, the depth of 10 km on our seismic lines to the northeast of ECr11 moves toward the trench axis. Previous results for lines KPr1, DAr5, and DAr2 in the northernmost trench area (Nishizawa et al 2009) also support trenchward positions of the 10-km contour.…”
Section: Subduction Of the Philippine Sea Platesupporting
confidence: 59%
See 1 more Smart Citation
“…However, the depth of 10 km on our seismic lines to the northeast of ECr11 moves toward the trench axis. Previous results for lines KPr1, DAr5, and DAr2 in the northernmost trench area (Nishizawa et al 2009) also support trenchward positions of the 10-km contour.…”
Section: Subduction Of the Philippine Sea Platesupporting
confidence: 59%
“…Another characteristic in the gravity map is that there are two low gravity anomaly belts parallel to the trench. One of the low gravity belts is along the trench axis, and the other one is in the (Nishizawa et al 2009). A non-tuned airgun array with a capacity of 6000 (1500 × 4) cubic inch (98.3 L) was shot for the refraction survey and a 1050 (350 × 3) cubic inch (17.2 L) airgun cluster was used for the multichannel reflection survey.…”
Section: Introductionmentioning
confidence: 99%
“…The Kyushu Mountains are the northern extension of KyushuPalau Ridge. Nishizawa et al (2009) showed the existence of a thick oceanic crust related to the subducting KyushuPalau Ridge in the eastern part of the Hyuganada region. They observed a low-velocity zone (V p = 6.0-6.8 km/s) at the oceanic middle crust (10-15 km depth).…”
Section: Beneath the Kyushu Mountainsmentioning
confidence: 99%
“…The northwestern end of the plateau is currently subducting beneath the Ryukyu (Nansei-Shoto) Trench (Nishizawa et al 2009). Igneous rocks obtained from the plateau suggest that its pedestal is Cretaceous in age, and the ridge portion situated on the pedestal formed in the Middle Eocene (Tokuyama et al 1986;Ishizuka and Yuasa 2007).…”
Section: Introductionmentioning
confidence: 99%